The Knowledge Level with Community Compliance in Implementing Covid-19 Prevention Health Protocols: Knowledge Level with Community Compliance in Implementing - Dya Sustrami; sari, Ninik Ambar Sari; Hidayatus Sya’diyah; Dedi Irawandi (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2022)
Covid 19 is a type of virus that spreads very quickly or infects other people. Most Indonesians do not comply with the government's recommendation to comply with health protocols. The purpose of this study was to analyze the level of knowledge with compliance in the Covid-19 health protocol. This study used a cross sectional approach. Samples were taken by accidental sampling technique as many as 154 people in RW 03 Manukan Kulon Village, Surabaya City. The variable level of knowledge and compliance instrument used a questionnaire. Data were analyzed using Spearman Rho's test with a significance degree of 0.05. The results showed that there was a relationship between the knowledge level variable (0.040) and compliance with the Covid-19 health protocol in RW 03, Manukan Kulon Village, Surabaya. The level of knowledge is very influential on compliance in carrying out health protocols. The implication of this study is that the level of knowledge affects the community's compliance with health protocols.